Pedro Martinez - Schaefer, A. R. frey50 (Mankato, Minn. : Capstone High-Interest Books, 2002)
A brief biography of the Boston Red Sox pitcher who won the Cy Young Award in 1997 and 1999.
Keywords: 1971-; Martinez, Pedro, -- 1971-; Baseball players -- Dominican Republic -- Biography -- Juvenile Literature; Baseball players